Delayed SARS-COV-2 Viral Clearance in a Newly Diagnosed HIV Patient: A Case Series - Dimas Bayu Firdaus; Oea Khairsyaf; Dewi Wahyu; Irvan Medison; Deddy Herman; Masrul Basyar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: SARS-CoV-2 can infect anyone, but people with HIV have underlying conditions or comorbidities that can make them seriously ill if infected with SARS-CoV-2. HIV attacks and destroys the immune system delays the response of specific antibodies, and even causes failure to thrive, resulting in a long course of the disease. This case report aimed to describe 2 cases of HIV patients co-infected with SARS-CoV-2 with delayed viral clearance. Case presentation: There are two HIV patients with co-infection with SARS-CoV-2. The first patient, a 32-year-old man with COVID-19 and HIV-AIDS, was referred from a regional hospital after being treated for 10 days due to clinical deterioration. Physical examination showed that the patient's general condition was moderately ill, and other vital signs were within normal limits. Oral candidiasis was seen in the patient's mouth, crackles were found in both lung fields, and epigastric tenderness was found on abdominal examination. The patient tested positive for COVID-19 based on the results of an antigen swab examination from the previous hospital. The second patient, a 26-year-old man, came with complaints of intermittent fever 1 week before entering the hospital. Complaints began with the body feeling weak and coughing without phlegm 2 weeks ago. The patient tested positive for COVID-19 based on the results of an antigen swab examination. The delayed viral clearance of SARS-CoV-2 in the two patients was possibly caused by the impaired immune response due to HIV infection, as shown by the presence of lymphopenia and decreased CD4+. Conclusion: ARV use can suppress HIV viral load and increase immunity so that can help viral clearance of SARS-CoV-2.